Land-use changes may explain the recent range expansion of the Black-shouldered Kite Elanus caeruleus in southern Europe - Balbontín, Javier; Negro, Juan José; Sarasola, José Hernán; Ferrero, Juan José; Rivera, Domingo (Ibis, 2008)
Occasional observations of Black-shouldered Kites Elanus caeruleus in Europe date back to the mid-19th century, but it was only recorded as a breeding species in the early 1960s in Portugal and a few years later in neighbouring Spain. This recent colonization, possibly from Africa where the species is abundant, may be due to climate change, land-use changes in southern Europe, or both. As a ﬁrst step to understanding this range expansion process we have developed a habitat selection model using data from the current strongholds of its European distribution. Comparing the proportion of different habitat types around 46 breeding sites and 45 randomly chosen plots, we have found that the area of cultivated parklands known as dehesas in Spain is a strong predictor of the current distribution range of breeding pairs of Black-shouldered Kites. Speciﬁcally, the percentage of dehesas with planted cereal and a low density of trees (i.e. < 7 trees/ha and thus a savannah-like habitat) within the study plots explained 44.6% of the residual deviance in our model. The minimal adequate model classiﬁed 81.3% of breeding sites and random plots correctly. Our results suggest that Black-shouldered Kites may have taken advantage of the gradual increase of cultivated dehesas in the second half of the 20th century to expand its range in Europe. This particular type of dehesa is structurally similar to the African savannahs where the species thrives and may offer a higher density of rodents than traditional dehesas, which primarily contain pastureland for livestock ranching
Keywords: colonization; Dehesa; habitat selection; Land-use change; occurrence models; raptors.

Land-use changes may explain the recent range expansion of the Black-shouldered Kite Elanus caeruleus in southern Europe - Balbontín, Javier; Negro, Juan José; Sarasola, José Hernán; Ferrero, Juan José; Rivera, Domingo (Ibis, 2008)
Occasional observations of Black-shouldered Kites Elanus caeruleus in Europe date back to the mid-19th century, but it was only recorded as a breeding species in the early 1960s in Portugal and a few years later in neighbouring Spain. This recent colonization, possibly from Africa where the species is abundant, may be due to climate change, land-use changes in southern Europe, or both. As a ﬁrst step to understanding this range expansion process we have developed a habitat selection model using data from the current strongholds of its European distribution. Comparing the proportion of different habitat types around 46 breeding sites and 45 randomly chosen plots, we have found that the area of cultivated parklands known as dehesas in Spain is a strong predictor of the current distribution range of breeding pairs of Black-shouldered Kites. Speciﬁcally, the percentage of dehesas with planted cereal and a low density of trees (i.e. < 7 trees/ha and thus a savannah-like habitat) within the study plots explained 44.6% of the residual deviance in our model. The minimal adequate model classiﬁed 81.3% of breeding sites and random plots correctly. Our results suggest that Black-shouldered Kites may have taken advantage of the gradual increase of cultivated dehesas in the second half of the 20th century to expand its range in Europe. This particular type of dehesa is structurally similar to the African savannahs where the species thrives and may offer a higher density of rodents than traditional dehesas, which primarily contain pastureland for livestock ranching
Keywords: colonization; Dehesa; habitat selection; Land-use change; occurrence models; raptors.